2008
DOI: 10.1080/09588220802447859
|View full text |Cite
|
Sign up to set email alerts
|

Learning English with The Sims: exploiting authentic computer simulation games for L2 learning

Abstract: With their realistic animation, complex scenarios and impressive interactivity, computer simulation games might be able to provide context-rich, cognitively engaging virtual environments for language learning. However, simulation games designed for L2 learners are in short supply. As an alternative, could games designed for the mass-market be enhanced with support materials to allow students to enter and make use of them for learning? This classroom-based investigation looked into whether the best selling game… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
145
2
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 220 publications
(171 citation statements)
references
References 18 publications
12
145
2
12
Order By: Relevance
“…Research in educational virtual reality reveals that 3D interactive environments provide support for constructivist-based learning activities by allowing learners to interact directly with information from a firstperson perspective (Bricken & Byrne, 1993;Dede, 1995). More recently, Ranalli (2008) considered the use of the MUVE SIMS as a virtual learning tool to increase language use and comprehension. Ranalli reports that virtual environments that provide language simulations are rich in natural associations that facilitate cohesive meaningful use of language.…”
Section: Virtual Reality Environments and Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…Research in educational virtual reality reveals that 3D interactive environments provide support for constructivist-based learning activities by allowing learners to interact directly with information from a firstperson perspective (Bricken & Byrne, 1993;Dede, 1995). More recently, Ranalli (2008) considered the use of the MUVE SIMS as a virtual learning tool to increase language use and comprehension. Ranalli reports that virtual environments that provide language simulations are rich in natural associations that facilitate cohesive meaningful use of language.…”
Section: Virtual Reality Environments and Learningmentioning
confidence: 99%
“…However, empirical research on the benefits or effects of MUVEs on ELLs' language development and speaking is limited (Garcia-Ruiz, Edwards, & Aquino-Santos, 2007;Ranalli, 2008;Zheng, Young, Brewer, & Wagner, 2009). Of the few studies available, it has been found that virtual environments have provided an enhanced learning environment (e.g., Barkand & Kush, 2009;Peterson, 2006;Zheng et al, 2009).…”
Section: Virtual Reality Environments and Learningmentioning
confidence: 99%
See 3 more Smart Citations